Perceptions of the usefulness of Choosing Wisely among general practitioners in Norway: a nationwide survey - Jørgen Breivold; Karin Isaksson Rø; Stein Nilsen; Stefán Hjörleifsson (BMC Primary Care)
Abstract Background Choosing Wisely is an international initiative to curb medical overuse. The Norwegian College of General Practice has published recommendations to avoid commonly used services for safer healthcare. This study investigated Norwegian GPs’ perceptions of Choosing Wisely. Methods Cross-sectional online survey of Norwegian GPs in 2021. We report GPs’ perceptions of Choosing Wisely recommendations as proportions, using multiple ordinal regression to assess factors influencing the campaign’s perceived usefulness. Results Responses from 900 GPs, with a response rate of 18% were included. 81% were aware of Choosing Wisely, and of these 82% found the campaign somewhat or very useful in reducing overdiagnosis or overtreatment. This correlated with lower levels of work-related stress (adjusted odds ratio (AOR) 0.61, 95% confidence interval (CI) 0.45–0.83) and more frequently reaching an agreement with patients to avoid unnecessary medical activities (AOR 1.93, 95% CI 1.26–2.95). More frequently reaching agreement with patients was also associated with finding the campaign very useful (AOR 2.21, 95% CI 1.51–3.24). Among those who did not find the campaign useful, 74% stated that this could partly be due to the campaign’s inability to influence patients’ opinions. 90% of the GPs who were aware of the campaign had implemented one or more recommendations. Conclusions Choosing Wisely appears to be considered useful by a substantial proportion of Norwegian GPs. Since the effectiveness of the campaign seems to be linked to the ability to manage gatekeeping, it may be beneficial to bolster the gatekeeping role of GPs and raise public awareness of medical overuse.